Author Correction: Study of 300,486 individuals identifies 148 independent genetic loci influencing general cognitive function - Gail Davies (Nature Portfolio, 2019)
Christina M. Lill, who contributed to analysis of data, was inadvertently omitted from the author list in the originally published version of this article. This has now been corrected in both the PDF and HTML versions of the article.